Seroprevalence of Neospora caninum and Toxoplasma gondii infections in aborted cattle in Hamedan, Iran - Gharekhani, Jamal (Journal of Advanced Veterinary and Animal Research, 2014)
The aim of current study was to assess the seroprevalence of Neospora (N.) caninum and Toxoplasma (T.) gondii infections in aborted cattle and subsequent estimation of role of these parasites in cattle abortion in Hamedan province, Iran. Blood samples (n=85) of aborted cattle were collected from different locations of Hamedan province for a period of two years from January, 2010 to December, 2012. All the samples were evaluated for the presence of IgG-antibodies against N. caninum and T. gondii using Enzyme Linked Immuno Sorbent Assay (ELISA). The results showed that 61.2% (n=52/85), 5.9% (n=5/85) and 3.5% (n=3/85) animals were positive for N. caninum, T. gondii and co-infection of these two, respectively. There was no significant correlation between seroprevalence rates, age groups and breeding (p>0.05). However, a significant difference was found between T. gondii infection and the type of cattle (p=0.05), unlike to N. caninum (p=0.52). This is the first report of N. caninum and T. gondii co-infection in cattle in Iran. Although the rate of T. gondii infection was lower but this parasite might partly be responsible to be transmitted to humans. Further investigations and appropriate control strategies in management of cattle farms are highly recommended. DOI: http://dx.doi.org/10.5455/javar.v1i2p32-35 J. Adv. Vet. Anim. Res., 1(2): 32-35, June 2014